2021
DOI: 10.1002/ppap.202000249
|View full text |Cite|
|
Sign up to set email alerts
|

Gas‐phase chemistry and reactive‐ion etching kinetics for silicon‐based materials in C4F8 + O2 + Ar plasma

Abstract: In this study, we investigated the effects of C4F8/O2 and Ar/O2 component ratios in C4F8 + O2 + Ar gas system on plasma parameters, gas‐phase chemistry, and etching kinetics for Si, SiO2, and Si3N4 under the condition of inductively coupled radiofrequency (13.56 MHz) plasma. The use of plasma diagnostics by Langmuir probes, together with the zero‐dimensional plasma modeling, allowed one to compare two different gas mixing regimes in respect to (a) electrons‐ and ions‐related plasma parameters; (b) steady‐state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The set of chemical reaction with corresponding rate coefficients for each gas mixture was taken from our previous model-based works dealt with CF 4 + Ar/O 2 , refs. [ 13 , 17 , 23 ] CHF 3 + Ar/O 2 [ 31 ] and C 4 F 8 + Ar/O 2 [ 13 , 32 ] plasmas. Earlier, these kinetic schemes have been used by several authors and demonstrated the decent similarity between model-predicted and measured F atom densities [ 11 ].…”
Section: Experimental and Modeling Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The set of chemical reaction with corresponding rate coefficients for each gas mixture was taken from our previous model-based works dealt with CF 4 + Ar/O 2 , refs. [ 13 , 17 , 23 ] CHF 3 + Ar/O 2 [ 31 ] and C 4 F 8 + Ar/O 2 [ 13 , 32 ] plasmas. Earlier, these kinetic schemes have been used by several authors and demonstrated the decent similarity between model-predicted and measured F atom densities [ 11 ].…”
Section: Experimental and Modeling Detailsmentioning
confidence: 99%
“…The similar rule can also be applied to other ion-driven effects on the etched surface, such as the removal of the fluorocarbon polymer film, the destruction of chemical bonds between surface atoms, and the ion-stimulated desorption of low volatile reaction products. The rate of heterogeneous chemical reaction [ 22 , 23 , 32 , 40 ], where is the fluorine atom flux, is the effective reaction probability [ 9 , 10 , 11 ], is the fraction of adsorption sites occupied by chemically inert species, is the fraction of vacant adsorption sites, and is the sticking coefficient of etchant species to the vacant adsorption site. That is why the parameter is not only the exponential function of surface temperature (as it typically takes place for the spontaneous reaction mechanism) but also depends on many plasma-related factors that retard or accelerate the chemical reaction through the change in .…”
Section: Experimental and Modeling Detailsmentioning
confidence: 99%